Gastric Cancer Accompanying Plummer-Vinson Syndrome - Ho Joon Im; Sung Eun Kim; Moo In Park; Seun Ja Park; Won Moon; Jae Hyun Kim; Kyoungwon Jung; Jung Gu Park (Yong Chan Lee, 2020)
Plummer-Vinson syndrome (PVS), also called sideropenic dysphagia or Paterson-Kelly syndrome, is a condition characterized by a triad of chronic iron-deficiency anemia, esophageal webs, and dysphagia. This syndrome is considered as a precancerous condition due to the occurrence of squamous cell carcinoma in the hypopharynx, upper esophagus and oral cavity. Although exact data on the prevalence of the syndrome are not evidently available, physicians need to recognize this rare syndrome. Most of the patients are elderly Caucasian women aged 40 to 70 years, but cases in children, adolescents, or men have also been described. At present, the prevalence of PVS is decreasing due to improvement in nutritional habits and intake of iron supplements. Therefore, the syndrome accompanied with gastric cancer is even more uncommon. We report a case of a 61-year-old woman with PVS who was diagnosed with gastric cancer and improved after treatment.